Blockchain and regenerative finance: charting a path toward regeneration - Schletz, Marco; Constant, Axel; Hsu, Angel; Schillebeeckx, Simon; Beck, Roman; Wainstein, Martin (Frontiers in Blockchain, 2023)
The Regenerative Finance (ReFi) movement aims to fundamentally transform the governance of global common pool resources, such as the atmosphere, which are being degraded despite international efforts. The ReFi movement seeks to achieve this by utilizing digital monitoring, reporting, and verification (D-MRV), tokenization of assets, and decentralized governance approaches.However, there is currently a lack of a clear path forward to create and implement models that actually drive the 'Re-' in ReFi, beyond perpetuating the existing extractive economics and towards actual regeneration. In addition, ReFi suffers from growing pains, lacking a common interoperability framework and definition for determining what a ReFi project is and how do the individual components align toward the grand ambition.This paper provides a definition of the ReFi stack of interconnected components and examines how it can address limitations in climate change accounting, finance and markets, and governance. The authors also examine the theory of regenerative economics and common pool resources to encourage further discussions and advancements in the ReFi space. The crucial question remains if and how ReFi can drive a change in paradigm toward the effective regeneration of global common pool resources.